PERSEPSI, PENGETAHUAN, DAN PERILAKU MEMBACA KORAN ONLINE PADA MAHASISWA - Novitasari, Leli Dwi; Djamaludin, Moh. Djemdjem; Johan, Irni Rahmayani (Jurnal Ilmu Keluarga dan Konsumen, 2013)
This study aimed to analyze the correlation between college students characteristic, family characteristic, perception, knowledge, families behavior, peer groups behavior, and college student behavior in reading online newspaper. This study involved 100 college students that were choosed by convenience method. Data was collected by self report. The results showed that college students had knowledge and perception of online newspaper in moderate category. Students knowledge correlated significantly with father occupation, while perception correlated significantly with gender and father occupation. Meanwhile, family and peer groups behavior in reading online newspaper in low category. Family behavior in reading online newspaper correlated significantly with money pocket, income, and mother occupation. Students behavior in reading online newspaper was measured by duration and frequency. Students reading online newspaper less than one hour with frequency at unpredictable time. Based on duration, students behavior correlated significantly with perception, while based on frequency, students behavior correlated significantly with family size and family income.